Effect of N ancillary ligands on the structure, nuclearity and magnetic behavior of Cu(ii)–pyrazolecarboxylate complexes. (17th November 2016) - Cheng, Meiling; Sun, Lin; Han, Wei; Wang, Shen; Liu, Qi; Sun, Xiaoqiang; Xi, Haitao
Abstract : The first discrete cyclic-trinuclear copper(ii )–pyrazolato complex without any μ3 ligand core was synthesized and its magnetic properties were investigated. Abstract : In the absence/presence of different N ancillary ligands, four copper(ii )-pyrazolecarboxylate complexes, [Cu(HMPCA)2 (ImH)2 ]·2H2 O (1 ), [Cu2 (MPCA)2 (H2 O)4 ] (2 ), [Cu2 (MPCA)2 (4, 4′-bpy)(H2 O)2 ] n ·5 n H2 O (3 ) and [Cu3 (MPCA)3 (Phen)3 ]2 ·2EtOH·15H2 O (4 ) (H2 MPCA = 5-methyl-1 H -pyrazole-3-carboxylic acid, ImH = imidazole, 4, 4′-bpy = 4, 4′-bipyridine and Phen = 1, 10-phenanthroline) were obtained. All complexes have been structurally characterized. Compounds2 and3 containing the same bis(μ-pyrazolato)dicopper(ii ) planes range from dinuclear to 1D polymer. Trinuclear complex4 contains the first reported cyclic-trinuclear copper(ii )–pyrazolato structure without any μ3 ligand core. Magnetic susceptibility data show that complexes2–4 exhibit antiferromagnetic couplings between the adjacent magnetic centers.